Human innate lymphoid cells (ILCs) in filarial infections. (15th June 2017) - Bonne‐Année, S.; Nutman, T. B.
Summary: Filarial infections are characteristically chronic and can cause debilitating diseases governed by parasite‐induced innate and adaptive immune responses. Filarial parasites traverse or establish niches in the skin (migrating infective larvae), in nonmucosal tissues (adult parasite niche) and in the blood or skin (circulating microfilariae) where they intersect with the host immune response. While several studies have demonstrated that filarial parasites and their antigens can modulate myeloid cells (monocyte, macrophage and dendritic cell subsets), T‐ and B‐lymphocytes and skin resident cell populations, the role of innate lymphoid cells during filarial infections has only recently emerged. Despite the identification and characterization of innate lymphoid cells (ILCs) in murine helminth infections, little is actually known about the role of human ILCs during parasitic infections. The focus of this review will be to highlight the composition of ILCs in the skin, lymphatics and blood; where the host‐parasite interaction is well‐defined and to examine the role of ILCs during filarial infections.